Evidence of band bending induced by hole trapping at MAPbI3 perovskite/metal interface. Issue 44 (28th October 2016) - Chen, Y.-F.; Tsai, Y.-T.; Bassani, D. M.; Clerc, R.; Forgács, D.; Bolink, H. J.; Wussler, M.; Jaegermann, W.; Wantz, G.; Hirsch, L.
Abstract : Unexpected band bending at the Au/MAPbI3 interface induced by the trapping of holes. Abstract : Electron injection by tunneling from a gold electrode and hole transport properties in polycrystalline MAPbI3 has been investigated using variable temperature experiments and numerical simulations. The presence of a large and unexpected band bending at the Au/MAPbI3 interface is revealed and attributed to the trapping of holes, which enhances the injection of electrons via tunneling. These results elucidate the role of volume and interface defects in state-of-the-art hybrid perovskite semiconductors.